2011
DOI: 10.1242/dev.056234
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs in early mammalian development: from gametes to gastrulation

Abstract: Small non-coding RNAs, including microRNAs (miRNAs), endogenous small interfering RNAs (endo-siRNAs) and Piwiinteracting RNAs (piRNAs), play essential roles in mammalian development. The function and timing of expression of these three classes of small RNAs differ greatly. piRNAs are expressed and play a crucial role during male gametogenesis, whereas endo-siRNAs are essential for oocyte meiosis. By contrast, miRNAs are ubiquitously expressed in somatic tissues and function throughout post-implantation develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 121 publications
1
115
0
2
Order By: Relevance
“…Our findings suggest that endo-siRNAs and/or tRNA-derived sRNAs might be the main sRNA regulators in early evolution of eukaryotes or if canonical miRNA does not exist. This scenario is reminiscent of tRNA-derived sRNAs and/ or endo-siRNAs/Piwi-interacting RNAs, which might be the main regulators in germ cell and very early developmental stages, but miRNAs do not function in these stages (35)(36)(37). Therefore, to better understand the functions of siRNAs and miRNAs in the differentiation regulation of protozoan and metazoan, respectively, we will need additional insight into the evolution of these cell differentiation regulators.…”
Section: Sgr-andmentioning
confidence: 99%
“…Our findings suggest that endo-siRNAs and/or tRNA-derived sRNAs might be the main sRNA regulators in early evolution of eukaryotes or if canonical miRNA does not exist. This scenario is reminiscent of tRNA-derived sRNAs and/ or endo-siRNAs/Piwi-interacting RNAs, which might be the main regulators in germ cell and very early developmental stages, but miRNAs do not function in these stages (35)(36)(37). Therefore, to better understand the functions of siRNAs and miRNAs in the differentiation regulation of protozoan and metazoan, respectively, we will need additional insight into the evolution of these cell differentiation regulators.…”
Section: Sgr-andmentioning
confidence: 99%
“…A key component of the RNAi machinery is the RNA-induced silencing complex (RISC), 2 which, in its minimal form, is composed of an Argonaute protein and a small noncoding RNA (ncRNA) of ϳ22-30 nucleotides in length. The biogenesis of RISC and its activities have been extensively reviewed elsewhere (2,3); simply stated, using its small ncRNA component as a guide sequence, an RNA-loaded RISC targets a complementary mRNA and elicits gene silencing via RNA degradation or a reduction in mRNA translation (4 -6).…”
mentioning
confidence: 99%
“…1). miRNA and siRNA biogenesis has been well described (2,3), whereas piRNA biogenesis is less well understood and in part involves the processing of single-stranded RNAs by yet identified ribonuclease(s) (9). Once assembled, piRISCs are thought to act primarily to silence cellular mobile genetic elements (e.g.…”
mentioning
confidence: 99%
“…The relationship between miRNAs and piRNAs in the early stages of development is summarized in a review article. 23 A recent study showed that miRNAs play roles in the biogenesis and stability of Drosophila piRNAs. 24 In mammals, it remains unclear how piRNAs are generated, although it is certain that the biogenesis pathway of piRNAs is distinct from that of miRNAs.…”
Section: Discussionmentioning
confidence: 99%